Self-reflexiveness in Photo-film Form as Illustrated by Zbigniew Czapla’s "Paper Box" - Justyna Sulejewska (Images)
The article interprets Paper Box by Zbigniew Czapla as an example of iconographic film and suggests that the genre be renamed photo-film. An analysis of particular means of film expression and photographic metaphors leads to seeing photo-film as a synthesis of various media, going beyond the world of cinema in terms of genealogy.